(a+6)(a*2-8a+8)=

Simple and best practice solution for (a+6)(a*2-8a+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a+6)(a*2-8a+8)= equation:


Simplifying
(a + 6)(a * 2 + -8a + 8) = 0

Reorder the terms:
(6 + a)(a * 2 + -8a + 8) = 0

Reorder the terms for easier multiplication:
(6 + a)(2a + -8a + 8) = 0

Reorder the terms:
(6 + a)(8 + 2a + -8a) = 0

Combine like terms: 2a + -8a = -6a
(6 + a)(8 + -6a) = 0

Multiply (6 + a) * (8 + -6a)
(6(8 + -6a) + a(8 + -6a)) = 0
((8 * 6 + -6a * 6) + a(8 + -6a)) = 0
((48 + -36a) + a(8 + -6a)) = 0
(48 + -36a + (8 * a + -6a * a)) = 0
(48 + -36a + (8a + -6a2)) = 0

Combine like terms: -36a + 8a = -28a
(48 + -28a + -6a2) = 0

Solving
48 + -28a + -6a2 = 0

Solving for variable 'a'.

Factor out the Greatest Common Factor (GCF), '2'.
2(24 + -14a + -3a2) = 0

Factor a trinomial.
2((4 + -3a)(6 + a)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(4 + -3a)' equal to zero and attempt to solve: Simplifying 4 + -3a = 0 Solving 4 + -3a = 0 Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3a = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3a = 0 + -4 -3a = 0 + -4 Combine like terms: 0 + -4 = -4 -3a = -4 Divide each side by '-3'. a = 1.333333333 Simplifying a = 1.333333333

Subproblem 2

Set the factor '(6 + a)' equal to zero and attempt to solve: Simplifying 6 + a = 0 Solving 6 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + a = 0 + -6 Combine like terms: 6 + -6 = 0 0 + a = 0 + -6 a = 0 + -6 Combine like terms: 0 + -6 = -6 a = -6 Simplifying a = -6

Solution

a = {1.333333333, -6}

See similar equations:

| 6c^2+7cd-5d^2= | | 2(x+3)-3x=5-x+1 | | 2x+5+6x-20=180 | | 8x-2(x+5)=5(2x-6) | | 9x-3y=27 | | 6a-47-2a=8a-15 | | 6x-5=-2x+11 | | 3(x+4)-2(x-1)=4(x+4) | | 75-3n+6n=12+15n-2+3n+20 | | -5+3m=3-m | | -3(-2)+6+-2= | | -1+3(x-1)=8x-5(x-2)-14 | | 7x-40-27x=10x+6+36 | | x^2+18x+53=594 | | x^2-5x-11x=0 | | 9x-7=4x+1 | | 9d-4=49 | | 30x=-480 | | x+x*.05=1065.64 | | x+x*.05=1000 | | 3x-17=-14 | | x-16=-30 | | 25w^2-10w+1=0 | | 7-p=3+3p | | 8t-6(-2+7t)=9+t-11 | | X+(X*0.05)=1000 | | 4(5)x-2(3)y=13 | | x^2-2x-6= | | 3y+2y-5=15+y | | X+22=84 | | 10p-6=(-36) | | 2-3(r-7)-7r=4(r-2)+8 |

Equations solver categories